Development And Assessment Of Power-Based Walnut Kernel Grader - Farooq, Faizan; Singh, Amrit Pal; Hussain, Syed Zameer; Ashraf, Arselan; Rather, Mohammad Ashraf; Sophian, Ali (2021)
Kernel grading is considered one of the hectic labor processes in terms of nuts arrangement and classification. This paper aims to develop a mechanized system that will liberate the exhaustion of human resources and perform with promising output in terms of grading. This paper is focused on the grading of walnut kernels. Walnut is one of the main mild nuts produced all around the world. The model has been developed to grade the walnut kernels to segregate them in terms of size. The grading of walnut kernels is a layer-wise process separating the kernels into three classes. The workflow of the system starts execution with a hopper, which is used for collecting the walnut kernels. It is followed by the three perforated trays which are used to separate the walnut kernels into three classes based on size. This model provides the output from three vents attached with three perforated trays based on size.The experimental accuracy of our system came out to be 99% which proves the effectiveness of this work. The model has also been evaluated on the other performance parameters displayed in the results section of this paper.